High molar activity [18F]tetrafluoroborate synthesis for sodium iodide symporter imaging by PET - Dmitry Soloviev; Piotr Dzien; Agata Mackintosh; Gaurav Malviya; Gavin Brown; David Lewis (SpringerOpen, 2022)
Abstract Background Sodium iodide symporter (NIS) imaging by positron emission tomography (PET) is gaining traction in nuclear medicine, with an increasing number of human studies being published using fluorine-18 radiolabelled tetrafluoroborate ([18F]TFB). Clinical success of any radiotracer relies heavily on its accessibility, which in turn depends on the availability of robust radiolabelling procedures providing a radiotracer in large quantities and of high radiopharmaceutical quality. Results Here we publish an improved radiolabelling method and quality control procedures for high molar activity [18F]TFB. The use of ammonium hydroxide for [18F]fluoride elution, commercially available boron trifluoride-methanol complex dissolved in acetonitrile as precursor and removal of unreacted [18F]fluoride on Florisil solid-phase extraction cartridges resulted in the reliable production of [18F]TFB on SYNTHRA and TRACERLAB FXFN automated synthesizers with radiochemical yields in excess of 30%, radiochemical purities in excess of 98% and molar activities in the range of 34-217 GBq/µmol at the end of synthesis. PET scanning of a mouse lung tumour model carrying a NIS reporter gene rendered images of high quality and improved sensitivity. Conclusions A novel automated radiosynthesis procedure for [18F]tetrafluoroborate has been developed that provides the radiotracer with high molar activity, suitable for preclinical imaging of NIS reporter gene.